Secret, silent screams - Nixon, Joan Lowery (New York : Delacorte Press, 1988)
A high school senior is convinced her friend Barry did not commit suicide but was a murder victim, and she endangers her own life to prove it.
Booklist.
Bulletin (Center for Children's books).
School Library Journal.
5.7
5.7
7-10.
Keywords: Mystery and detective stories; Suicide -- Fiction; Mystery fiction; Suicide -- Fiction